2019
DOI: 10.1007/s40259-019-00343-8
|View full text |Cite
|
Sign up to set email alerts
|

PF-06881893 (Nivestym™), a Filgrastim Biosimilar, Versus US-Licensed Filgrastim Reference Product (US-Neupogen®): Pharmacokinetics, Pharmacodynamics, Immunogenicity, and Safety of Single or Multiple Subcutaneous Doses in Healthy Volunteers

Abstract: Background Three comparative clinical studies assessed the pharmacokinetics (PK), pharmacodynamics (PD), immunogenicity and safety of PF-06881893 (filgrastim-aafi; Nivestym™), a filgrastim biosimilar, versus US-licensed reference product (filgrastim; US-Neupogen ® ) in healthy volunteers (HVs). Methods Two separate open-label, crossover-design PK/PD studies were conducted: a single-dose study ( n = 24) and a multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
1
7
0
1
Order By: Relevance
“…The inclusion of patients may make the comparison nonsensitive due to the interference of disease and comedication. The selected dose of 300 µg was close to a daily dose of 5 mg/kg/day of most therapeutic indications 9‐12,14‐19 . The method for quantification of filgrastim in serum was adequately validated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion of patients may make the comparison nonsensitive due to the interference of disease and comedication. The selected dose of 300 µg was close to a daily dose of 5 mg/kg/day of most therapeutic indications 9‐12,14‐19 . The method for quantification of filgrastim in serum was adequately validated.…”
Section: Discussionmentioning
confidence: 99%
“…Tinagrast, a proposed biosimilar filgrastim, was developed by AryaTinaGene Biopharmaceutical Company, and extensive comparability studies, including physicochemical characterization, cell‐based biological activity, and nonclinical studies, have suggested a high similarity to the originator product. As the study of pharmacokinetic and pharmacodynamic profile of a new filgrastim product in healthy volunteers is routinely performed in support of biosimilarity, 9‐12 the objective of the present study was to evaluate the similarity of 2 filgrastim products after a subcutaneous administration of a 300‐µg single dose, comparing their pharmacokinetic and pharmacodynamic and safety properties in healthy subjects.…”
mentioning
confidence: 99%
“…They are also key to guiding the requirement for, and nature of, subsequent comparative clinical studies [ 31 ]. The proportion of PK/PD queries was unaffected whether the study was conducted in patients (such as for PF-rituximab [ 32 ]) or in healthy subjects (PF-infliximab [Ixifi ™ ] [ 33 ], PF-epoetin [ 34 , 35 ], PF-filgrastim [ 36 ], PF-trastuzumab [ 37 ], PF-bevacizumab [ 38 ], PF-adalimumab [Abrilada ™ /Amsparity] [ 39 ], PF-pegfilgrastim [Nyvepria ™ ] [ 40 ]). The generally low focus on PK information across RAs may reflect the proactive engagement of the applicant with the relevant RA during the study design process, the transparency of the data disclosure and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Embora estudos comparativos entre produtos biológicos inovadores e suas respectivas cópias venham demonstrando semelhança quanto ao perfil de imunogenicidade 25,26,27,28,29,30 , a avaliação da imunogenicidade é recomendada para todos os medicamentos biológicos, inovadores e cópias, durante todo o ciclo de vida dos produtos 22 .…”
Section: Imunogenicidadeunclassified